2002
DOI: 10.1590/s0103-90162002000300008
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Metarhizium anisopliae (Metsch.) and Beauveria bassiana (Bals.) isolates to control Alabama argillacea (Huebner) caterpillars

Abstract: The cotton leafworm, Alabama argillacea (Huebner, 1818) (Lepidoptera: Noctuidae), is considered to be one of the key pests in herbaceous cotton (Gossypium hirsutum L. r. latifolium Hutch) cropping, with constant occurrence in all cotton-growing states of Brazil. In this study Metarhizium anisopliae and Beauveria bassiana isolates were screened and evaluated for pathogenicity against Alabama argillaceae. Initially, a screening of ten isolates of each fungus in a concentracion of 10(8) conidia mL-1, was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
4
2
Order By: Relevance
“…The B. bassiana CG138 isolate was the most effective against A. argillacea first-instar larvae, followed by the ESALQ 634 and CG 82 and CG 70 and ESALQ 645 as the least effective ( Table 2). Mortality of A. argillacea first-instar larvae with the GC 138 isolate was higher than that found (81, 74 and 40%) for third instar larvae of this species, with conidial suspension of B. bassiana strains UFRPE 645 (10 9 conidia mL -1 ), UFRPE 604 (10 8 conidia mL -1 ) and UFRPE 634 (10 7 conidia mL -1 ), respectively (César Filho et al, 2002). These differences can be attributed to the inoculation and conidia concentration of this pathogen (Santoro et al, 2007), and to the larvae development stage (César Filho et al, 2002).…”
Section: Selection Of Isolatescontrasting
confidence: 60%
See 3 more Smart Citations
“…The B. bassiana CG138 isolate was the most effective against A. argillacea first-instar larvae, followed by the ESALQ 634 and CG 82 and CG 70 and ESALQ 645 as the least effective ( Table 2). Mortality of A. argillacea first-instar larvae with the GC 138 isolate was higher than that found (81, 74 and 40%) for third instar larvae of this species, with conidial suspension of B. bassiana strains UFRPE 645 (10 9 conidia mL -1 ), UFRPE 604 (10 8 conidia mL -1 ) and UFRPE 634 (10 7 conidia mL -1 ), respectively (César Filho et al, 2002). These differences can be attributed to the inoculation and conidia concentration of this pathogen (Santoro et al, 2007), and to the larvae development stage (César Filho et al, 2002).…”
Section: Selection Of Isolatescontrasting
confidence: 60%
“…Mortality of A. argillacea first-instar larvae with the GC 138 isolate was higher than that found (81, 74 and 40%) for third instar larvae of this species, with conidial suspension of B. bassiana strains UFRPE 645 (10 9 conidia mL -1 ), UFRPE 604 (10 8 conidia mL -1 ) and UFRPE 634 (10 7 conidia mL -1 ), respectively (César Filho et al, 2002). These differences can be attributed to the inoculation and conidia concentration of this pathogen (Santoro et al, 2007), and to the larvae development stage (César Filho et al, 2002). Neonate larvae differ in scale, metabolism, digestive physiology, sensory modalities and intestinal microbiota from those of the late stages (Mason and Raffa, 2014;Despland, 2018).…”
Section: Selection Of Isolatescontrasting
confidence: 60%
See 2 more Smart Citations
“…Treating 2 nd instar larvae of S. exigua by M. anisopliae resulted in a relatively low pupal deformation percentage of 9.41and 4.17% respectively, while there were no deformities in case of the control group (table 3). Filho et al (2002) screened for the Pathogenicity of Metarhizium anisopliae and Beauveria bassiana isolates against Alabama argillaceae in Brazil at 27 ± 2 o C, RH 70 ± 5%. They found that mortalities caused by the M. anisopliae isolates at the different concentrations ranged from 4.5 to 91.2%.…”
Section: Effect Of Metarhizium Anisopliae On the Biological Aspects O...mentioning
confidence: 99%